2021
DOI: 10.3389/fpubh.2021.756717
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multimorbidity Subgroups on the Health Care Use and Clinical Outcomes of Patients With Tuberculosis: A Population-Based Cohort Analysis

Abstract: Background: Multimorbidity is defined as the existence of two or more chronic health conditions in the same individual. While patients with tuberculosis commonly have multiple conditions at diagnosis, such as HIV, diabetes, and depression, to the authors' knowledge, there is limited information on the patterns of multimorbidity, and how the types and combinations of conditions could impact the healthcare utilization, expenditure, and TB outcomes.Methods: An observational cohort study of adult patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Our study found a 52% prevalence of multimorbidity and 30.6% prevalence of more than two chronic conditions among TB patients. Similar to our findings, Chen et al in their study in China observed 38.6% and 21.2% whereas Karl et al in South Africa reported 26.9% and 25.3% prevalence of multimorbidity and two or more chronic conditions respectively among TB patients [ 9 , 18 ]. This suggest multimorbidity to be a norm rather than exception among TB patients, especially among the high TB burden countries in the world.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found a 52% prevalence of multimorbidity and 30.6% prevalence of more than two chronic conditions among TB patients. Similar to our findings, Chen et al in their study in China observed 38.6% and 21.2% whereas Karl et al in South Africa reported 26.9% and 25.3% prevalence of multimorbidity and two or more chronic conditions respectively among TB patients [ 9 , 18 ]. This suggest multimorbidity to be a norm rather than exception among TB patients, especially among the high TB burden countries in the world.…”
Section: Discussionsupporting
confidence: 91%
“…TB multimorbidity may represent a substantial burden for individuals, increasing their risk of adverse events and unfavorable outcomes ultimately affecting the already constrained healthcare system [ 9 ]. It poses a primary concern for healthcare system in India which is typically focused to manage single conditions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the gaps in the literature with regards to primary studies, our meta-review also highlights the lack of systematic reviews focused on people with TB and more than one additional chronic condition, which is an increasingly likely scenario as the prevalence of NCDs in LMICs grows. 2 In this regard, several cohort studies have assessed the impact of multimorbidity on TB treatment outcomes, such as in China or Brazil 31 32 finding worse outcomes among patients with multiple additional chronic conditions. Furthermore, Chen et al’s 31 results highlight that some combinations of comorbidities, such as the group with cardiovascular morbidity with complications, increase the risk of negative TB treatment outcomes more than others.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In this regard, several cohort studies have assessed the impact of multimorbidity on TB treatment outcomes, such as in China or Brazil 31 32 finding worse outcomes among patients with multiple additional chronic conditions. Furthermore, Chen et al’s 31 results highlight that some combinations of comorbidities, such as the group with cardiovascular morbidity with complications, increase the risk of negative TB treatment outcomes more than others. Considering the potential multiple-way synergies between multiple chronic conditions, a systematic review of the literature on this topic is sorely needed.…”
Section: Discussionmentioning
confidence: 99%
“…The Ningbo Regional Health Care Database (NRHCD), a standardized medical information network in Ningbo, China, collects and integrates electronic health records from hospitals and community clinics in the jurisdiction. In 2016, the platform reached the top level in the regional health information interconnection standardization and maturity measurement of the National Health Commission (18)(19)(20). By 2019, the platform covered all 65 public hospitals and 154 primary medical institutions.…”
Section: Data Sourcesmentioning
confidence: 99%